Webometrics Standards As A Tool To Improve The Ranking Of Syrian Universities - غدير , باسم; الشوا, سناء (Latakia University Journal - Economic and Legal Sciences Series, 2020)
One Of The Most Famous And Comprehensive Academic Rankings Of Universities Is The Webometrics, Which Includes About 30000 Universities And Academic Institutions Around The World, And It Is Interested In Classifying Universities According To Their Presence On The Internet Through Its Website. This Research Aimed To Study The Webometrics And Its Standards, In Order To Benefit From Them In Improving The Ranking Of Syrian Universities On The Internet. The Researcher Used Classification Data During Previous Versions To Find Out The Current Reality Of The Classification Of Syrian Universities, And What Is Their Ranking Locally, Arab, And Globally, And The Study Concluded That Webometrics Standards Are Not Considered To Be Complex Criteria That Are Difficult To Achieve Within The Current Reality Of The Capabilities Of Syrian Universities, And That Syrian Universities Have A Great Opportunity By Improving Its Global Rankings On Webometrics, If The Focus Is On Working With The Thrust Of These Standards On University Websites.